2020
DOI: 10.1101/2020.04.13.039826
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptic learning rules for sequence learning

Abstract: Remembering the temporal order of a sequence of events is a task easily performed by humans in everyday life, but the underlying neuronal mechanisms are unclear. This problem is particularly intriguing as human behavior often proceeds on a time scale of seconds, which is in stark contrast to the much faster millisecond time-scale of neuronal processing in our brains. One long-held hypothesis in sequence learning suggests that a particular temporal fine-structure of neuronal activity-termed "phase precession"-e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 65 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…In support of this, theta phase precession or theta sequences have been reported for cells responding to elapsed time (Pastalkova et al, 2008;Shimbo et al, 2021), or particular events or behaviors such as jumping , pulling a lever, or sampling an object (Terada et al, 2017;Aronov et al, 2017;Robinson et al, 2017), and has been observed in structures beyond the hippocampus (Kim et al, 2012;Hafting et al, 2008;Jones and Wilson, 2005;van der Meer and Redish, 2011;Tingley et al, 2018;Tang et al, 2021). These findings suggest that the theta phase code plays a role in supporting a wide array of cognitive functions, such as sequential learning (Lisman and Idiart, 1995;Skaggs et al, 1996;Reifenstein et al, 2021), prediction (Lisman and Redish, 2009;Kay et al, 2020) and planning (Johnson and Redish, 2007;Erdem and Hasselmo, 2012;Bolding et al, 2020;Bush et al, 2015).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In support of this, theta phase precession or theta sequences have been reported for cells responding to elapsed time (Pastalkova et al, 2008;Shimbo et al, 2021), or particular events or behaviors such as jumping , pulling a lever, or sampling an object (Terada et al, 2017;Aronov et al, 2017;Robinson et al, 2017), and has been observed in structures beyond the hippocampus (Kim et al, 2012;Hafting et al, 2008;Jones and Wilson, 2005;van der Meer and Redish, 2011;Tingley et al, 2018;Tang et al, 2021). These findings suggest that the theta phase code plays a role in supporting a wide array of cognitive functions, such as sequential learning (Lisman and Idiart, 1995;Skaggs et al, 1996;Reifenstein et al, 2021), prediction (Lisman and Redish, 2009;Kay et al, 2020) and planning (Johnson and Redish, 2007;Erdem and Hasselmo, 2012;Bolding et al, 2020;Bush et al, 2015).…”
Section: Introductionmentioning
confidence: 81%
“…These findings suggest that the theta phase code plays a role in supporting a wide array of cognitive functions. In particular, it has been proposed to underlie sequential learning (Lisman and Idiart, 1995;Skaggs et al, 1996;Reifenstein and Kempter, 2020), prediction (Lisman and Redish, 2009;Kay et al, 2020) and action planning (Johnson and Redish, 2007;Erdem and Hasselmo, 2012;Bolding et al, 2019;Bush et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the prevalence of phase precession due to its likely theoretical relevance as neuronal mechanism for binding and compressing sequential events. In brief, phase precession organizes spiking at time intervals below the deactivation time constant of NMDA receptors, facilitating synaptic plasticity between neurons that encode events at behavioral time-scales 7,10,24,[75][76][77] . Strengthening associations between consecutively active neurons may be a widely useful mechanism for learning associations.…”
Section: Discussionmentioning
confidence: 99%
“…To do this, we measured each neuron's rhythmic frequency of spiking in comparison to the local theta oscillation 49,50 . Identifying a consistent pattern of faster-than-LFP rhythmic spiking would indicate the presence of a precession-like pattern of LFP-coordinated spiking that could bind and compress sequential, non-spatial features of the task -just as spatial phase precession is theorized to do for locations 24,51 .…”
Section: Bmentioning
confidence: 99%
See 1 more Smart Citation